Effect of Losartan and Amlodipine on Heart Rate Variability In Essential Hypertensive Patients - Sultana, Shamima; Begum, Shelina; Ferdousi, Sultana; Ahmed, Mohammad Nesar Uddin (Journal of Bangladesh Society of Physiologist, 2014)
DOI: http://dx.doi.org/10.3329/jbsp.v8i2.18653 Bangladesh Soc Physiol. 2013, December; 8(2): 42-50